Infeksi Cacar Monyet (Monkeypox) - Larasati Budiyarto; Ayu Adzani Sabila; Hafizha Cyndriyani Putri (Jurnal Medika Hutama, 2023)
Monkeypox virus is one of the zoonotic viruses belonging to the genus Orthopoxvirus of the family Poxviridae. Case of monkeypox infection in human, also known as monkeypox, was first discovered at the Republic of the Congo in 1970. Monkeypox infection was previously an endemic disease, especially in Africa. This disease has become a global concern since WHO received reports of monkeypox cases originating from non-endemic countries in May 2022. The clinical signs and symptoms of the current monkeypox outbreak are considered different with the previous classic manifestations. Transmission of the disease is currently dominated by sexual contact. The diagnosis of monkeypox can be established through PCR examination. The mortality rate of monkeypox infection is low but may cause various complications. Until now, no specific treatment has been found for monkeypox infection. Vaccination after exposure is found to lower risk of severity and death. It is important for clinicians to study and understand more about the disease, prevention, outbreak control efforts, and management of monkeypox disease. Keywords : infection, management, monkeypox, prevention, transmission